Turning-off accidents between motor vehicles and cyclists. - (:unkn) unknown (My University, 2013)
One in four people killed on the roads in built-up areas is a cyclist. Turning-off accidents are the most common type of accident after turning-into / crossing accidents. The study shows that there is a need for action with regard to the design and layout of the infrastructure, encouraging road users to behave safely on the roads and improving their knowledge of the rules of the road.
Keywords: Straßenverkehr; Stadtverkehr; Fahrradverkehr; Individualverkehr; Autoverkehr; Verkehrssicherheit; Verkehrsunfall; Verkehrsverhalten; Verkehrsteilnehmer; Fahrradinfrastruktur; Radverkehrsführung; Unfallprävention; Unfallvermeidung; Radverkehrssicherheit; Knotenpunkt; Studie